The Effect of Sediment Texture on the Composition and Abundance of Microplastics in Banjaran River, Banyumas Regency, Indonesia - Yuliana, Andrie; Rahayu, Nur Laila; Zaenuri, Musyarif (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2024)
Plastic waste is a serious environmental problem for all countries in the world, including Indonesia. Plastic waste of various sizes can have a negative impact, especially microplastics. Microplastic contamination can be found in aquatic sediments. One of the waters potentially polluted by microplastics is the Banjaran River, Banyumas Regency. This research was conducted to determine the composition and abundance of microplastics as well as the effect of sediment texture on the composition and abundance of microplastics in the sediments of Banjaran River, Banyumas Regency. The research location was determined using purposive sampling at four stations. At each station, samples were taken randomly at three different places with three repetitions. Analysis of the composition and abundance of microplastics in sediments was done in a laboratory using microscope observation. Sediment texture analysis was done using a dry sieve and pipetting method. Five types of microplastics were found in all sediment samples with a predominance of fiber (35%), followed by fragments (29%), films (19%), pellets (10%) and foam (7%). The abundance of microplastics in sediments ranged from 2.3 to 4.86 particles/50 grams of dry sediment. The sediment texture that dominated the four stations was sand, with an average fraction proportion value of 86.62%. Sediment texture had the strongest effect on the composition of fragment-type microplastic at 50.2% and had the same impact on the overall abundance at 56%, which indicated that the sediment texture had a significant effect on these two variables.